(untitled) (Economics and region, 2024)
The article explores the possibilities of the Interreg Europe grant program funded by the European Union. It is emphasized that since Ukraine became a full-fledged partner of the Program only in 2024, two of the four grant competitions are relevant for Ukrainian communities, within which public authorities at all levels, non-profit organizations, and other public law entities have the opportunity to implement projects for a more effective regional development policy together with partners from EU member states and EU accession candidates. The study demonstrates the peculiarity of the Interreg Europe program, namely that projects that have a wide coverage (going beyond transnational territories), combine more and less developed regions, and cover regional development topics, namely: “Smart Europe”, “Green Europe”, “United Europe”, “Social Europe”, “Europe closer to citizens”, “Better Regional Governance”. The program can finance projects to be implemented by 5-16 partners with grant funding of up to EUR 1 to EUR 2 million. It is emphasized that the amount of the grant for one project cannot exceed 80% for public authorities of all levels and public law entities, and 70% for non-profit organizations. Project costs. Based on the results of the analysis of the goals, priorities of the Interreg Europe Program and all the eligibility criteria for the grant competition, as well as the formal requirements for the application, a number of recommendations have been developed and proposed for anyone who wants to use the program’s grants to implement regional development projects in Ukraine. To summarize: the impact of the project activities is obvious: individuals and organizations involved in regional development policy will increase their professional level by participating in Interreg Europe projects, they will be able to improve the development and implementation of their policies; institutions at the local, regional or national level will be more effective in implementing their regional development policies and programs.